Wajah Prakarsa Partisipatif: Dinamika Gagasan Reforma Agraria dan Gerakan Sosial di Indonesia Pasca 1998 - Aprianto, Tri Chandra (Jurnal Ilmu Sosial dan Ilmu Politik, 2008)
This paper reconstructs the ideas and processes of agrarian reform movement in the post reformation era. It has been developed into political agenda and adopted in state level policy. The pattern of movement, therefore, is going to create and to enlarge the creative transfornzation by pulling together the active reform actors (activists) in state level and social movement activist. Although the agrarian reform agenda has been adopted by the state, the quality of policy implementation is still indistinguishable. At this point, the activists started to combine the movement by distributing them into the state level andgrass roots movement. The agenda is aiming at proving the face of agrarian policy design and implementation that accomodates justice and sustainable development principles.